First Year Chemistry Laboratory Courses for Distance Learners: Development and Transfer Credit Acceptance - Brewer, Sharon E.; Cinel, Bruno; Harrison, Michelle; Mohr, Christina L. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
In delivering chemistry courses by distance, a key challenge is to offer the learner an authentic and meaningful laboratory experience that still provides the rigour required to continue on in science. To satisfy this need, two distance general chemistry laboratory courses appropriate for Bachelor of Science (B.Sc.) students, including chemistry majors, have been recently developed at Thompson Rivers University. A constructive alignment process was employed which clearly mapped learning outcomes and activities to appropriate assessment tools. These blended laboratory courses feature custom, home experimental kits and combine elements of online and hands-on learning. The courses were designed for flexible continuous enrollment and provide online resources including tutor support, instructional videos, lab report submission, and student evaluation. The assessment of students includes laboratory reports, safety quizzes, reflective journaling, digital photo documentation, and invigilated written and online practical exams. Emphasizing the quality and rigour in these distance laboratory learning experiences allowed both courses to be accepted for B.Sc. transfer credit by other institutions, an important criterion for students. This paper will outline the design and development process of these new blended laboratory courses, their course structures and assessments, and initial student results.